The Relationship between the Flexibility of the Torso with the Ability to Long Jump Hanging Style in Male Students of Class XI IPS SMA Negeri 4 Palembang - Kurnia, Rian Dwi; Kristina, Putri Cicilia; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
From observations made by researchers when sports learning with long jump material was underway, not many students can perform movement techniques in the long jump, especially the hanging style with a structure according to the teacher’s direction. This was seen when the PE teacher held daily exams at the second meeting, the result was that not many students were able to reach KKM which was 75. Of all the existing problems, related to the student’s ability to do the long jump hanging style, Researchers focused the problem on the low level of flexibility of the torso. This study aims to find out whether there is a relationship between the flexibility of the torso and the ability to long jump the hanging style in male students of class XI IPS SMA Negeri 4 Palembang. This research method uses the correlation method. The subjects of this study were 15 male students of class XI IPS SMA Negeri 4 Palembang. Data collection techniques use measurement tests. Data analysis using the product moment correlation formula. Based on data analysis that has been done by researchers, it can be concluded that there is a relationship between the flexibility of the torso with the ability to long jump hanging style in class XI social studies students of SMA Negeri 4 Palembang.